Albania : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
In this study, the following statistical data are presented in detail: GDP by sector of origin, construction of cost index, consumer price subsidies, agricultural production, production and yields of selected fruits, consumer price index, population, labor force, and employment, employment and wages in budgetary institutions, fiscal accounts, central government expenditure shares, tax revenue shares, interest rate shares, monetary survey, credit in state-owned banks, balance sheet of the bank of Albania, area under cultivation, production, and yields of selected agricultural crops, and so on.